The Effectiveness of the “Busuu Platform” in Improving the Writing Skills of 1st Grade Junior High School Students in Medan - Kezia Nur Elizanti Purba; Diah Safitri Armin (Universitas Cokroaminoto Palopo, 2025)
This study aims to investigate the effectiveness of the Busuu platform in improving the writing skills of 1st grade junior high school students. To address the issue of students' low English writing proficiency, a quasi-experimental design was used with pre-test and post-test control groups. The sample consisted of 40 students, divided equally into an experimental group that used the Busuu platform and a control group that received conventional instruction. Writing tests were administered before and after the treatment as the primary research instruments. The independent sample t-test showed a statistically significant difference between the groups' post-test results (p = 0.045), with the experimental group scoring an average of 81.75 and the control group 71.90. Although there was a slight decline from the experimental group’s pre-test average (82.50), their post-test performance remained higher than that of the control group. These findings indicate that the Busuu platform is effective in enhancing students’ writing skills. Therefore, it is recommended that teachers incorporate digital platforms like Busuu to foster more engaging and interactive English learning environments.